Activation by oxidation and ligand exchange in a molecular manganese vanadium oxide water oxidation catalyst. Issue 39 (7th September 2021) - Cárdenas, Gustavo; Trentin, Ivan; Schwiedrzik, Ludwig; Hernández-Castillo, David; Lowe, Grace A.; Kund, Julian; Kranz, Christine; Klingler, Sarah; Stach, Robert; Mizaikoff, Boris; Marquetand, Philipp; Nogueira, Juan J.; et al.
Abstract : Combined theoretical and experimental studies shed light on the initial steps of redox-activation of a molecular manganese vanadium oxide water oxidation catalyst. Abstract : Despite their technological importance for water splitting, the reaction mechanisms of most water oxidation catalysts (WOCs) are poorly understood. This paper combines theoretical and experimental methods to reveal mechanistic insights into the reactivity of the highly active molecular manganese vanadium oxide WOC [Mn4 V4 O17 (OAc)3 ] 3− in aqueous acetonitrile solutions. Using density functional theory together with electrochemistry and IR-spectroscopy, we propose a sequential three-step activation mechanism including a one-electron oxidation of the catalyst from [Mn2 3+ Mn2 4+ ] to [Mn 3+ Mn3 4+ ], acetate-to-water ligand exchange, and a second one-electron oxidation from [Mn 3+ Mn3 4+ ] to [Mn4 4+ ]. Analysis of several plausible ligand exchange pathways shows that nucleophilic attack of water molecules along the Jahn–Teller axis of the Mn 3+ centers leads to significantly lower activation barriers compared with attack at Mn 4+ centers. Deprotonation of one water ligand by the leaving acetate group leads to the formation of the activated species [Mn4 V4 O17 (OAc)2 (H2 O)(OH)] − featuring one H2 O and one OH ligand. Redox potentials based on the computed intermediates are in excellent agreement with electrochemical measurements at various solvent compositions. This intricate interplay between redox chemistry and ligand exchange controls the formation of the catalytically active species. These results provide key reactivity information essential to further study bio-inspired molecular WOCs and solid-state manganese oxide catalysts.